Impact of meniscus injury and chondromalacia on the patient‑reported quality of life, social support, and mental health following knee arthroscopy - Bartosz Turoń; Damian Małkowski; Maria Zabrzyńska; Krzysztof Buczkowski; Piotr Błaszak; Jakub Ohla; Michał Wilk; Janet Olagbaju; Agnieszka Witowska; Jan Zabrzyński (Videosurgery and Other Miniinvasive Techniques)
Introduction: Meniscal tears and chondromalacia patellae (CP) are among the most common knee pathologies treated with arthroscopic partial meniscectomy. Chronic knee pain impairs mobility, functionality, and the overall quality of life (QOL). Aim: The study evaluates the relationship between meniscus injury and early-stage CP found intraoperatively, and pre- and postoperative patient -reported QOL, perceived social support, and mental health. Materials and methods: Patients who underwent knee arthroscopy for meniscal and cartilage abnor mality, without reconstructive or restorative procedures, between 2019 and 2021, were prospectively enrolled in this study. Results: We observed a significant rise in the pre- and postoperative scores on the World Health Organization QOL Brief Version (WHOQOL -BREF) scale for various meniscal tears and different types of CP (grade 0–IV) in almost all domains. Education level did not significantly affect the WHOQOL -BREF assessment, and we found no statistical correlation between preoperative WHOQOL -BREF score in all domains and waiting time for surgery. However, there were significant differences between white- and blue-collar employees in the domains 1 and 2, that is, physical and psychological health. Conclusions:The study shows that the measured QOL improves in patients operated at the early stages of CP. Moreover, when both menisci are involved in the pathological process, the clinical outcomes are inferior. The education level and waiting time for surgery had no impact on QOL, contrary to the type of work, as white -collar workers had better outcomes in physical and psychological health domains.